Connexin hemichannel-mediated CO(2)-dependent release of ATP in the medulla oblongata contributes to central respiratory chemosensitivity - Huckstepp, Robert T R (Blackwell Science Inc, 2010)
Arterial [Image: see text], a major determinant of breathing, is detected by chemosensors located in the brainstem. These are important for maintaining physiological levels of [Image: see text] in the blood and brain, yet the mechanisms by which the brain senses CO(2) remain controversial. As ATP release at the ventral surface of the brainstem has been causally linked to the adaptive changes in ventilation in response to hypercapnia, we have studied the mechanisms of CO(2)-dependent ATP release in slices containing the ventral surface of the medulla oblongata. We found that CO(2)-dependent ATP release occurs in the absence of extracellular acidification and correlates directly with the level of [Image: see text]. ATP release is independent of extracellular Ca(2+) and may occur via the opening of a gap junction hemichannel. As agents that act on connexin channels block this release, but compounds selective for pannexin-1 have no effect, we conclude that a connexin hemichannel is involved in CO(2)-dependent ATP release. We have used molecular, genetic and immunocytochemical techniques to demonstrate that in the medulla oblongata connexin 26 (Cx26) is preferentially expressed near the ventral surface. The leptomeninges, subpial astrocytes and astrocytes ensheathing penetrating blood vessels at the ventral surface of the medulla can be loaded with dye in a CO(2)-dependent manner, suggesting that gating of a hemichannel is involved in ATP release. This distribution of CO(2)-dependent dye loading closely mirrors that of Cx26 expression and colocalizes to glial fibrillary acidic protein (GFAP)-positive cells. In vivo, blockers with selectivity for Cx26 reduce hypercapnia-evoked ATP release and the consequent adaptive enhancement of breathing. We therefore propose that Cx26-mediated release of ATP in response to changes in [Image: see text] is an important mechanism contributing to central respiratory chemosensitivity.